THE IMPACT OF DIGITAL TOOLS ON LANGUAGE TEACHING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article investigates the influence of digital tools on language instruction, with an emphasis on the ways in which technology improves instructional efficacy, accessibility, and learner engagement. It examines the advantages and prospective challenges of tools such as language learning apps, virtual classrooms, and AI-powered platforms in contemporary language education.